EFEKTIVITAS PROGRAM REHABILITASI HUTAN dan LAHAN (RHL) DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI SEKITAR HUTAN PELANGAN KABUPATEN LOMBOK BARAT - Chantika Dewi; Baiq Rizka Milania Ulfah (Yayasan Nusantara Hasana Berdikari, 2023)
The purpose of this study was to determine the effectiveness of the Forest and Land Rehabilitation (RHL) program in improving the economy of the community around the Pelangan forest. The data collection method used in this research is observation, interview, and literature study. The results of this study indicate that: the RHL program is effective in improving the economy of the community around the Pelangan forest, this can be seen from the absorption of labor both as laborers and as members of forest management farmer groups, where laborers earn wages for forest management, while farmer groups earn forest management products in the form of plantation products that can be sold and obtain plant seeds assistance